Limosilactobacillus reuteri ZY15 Alleviates Intestinal Inflammation and Barrier Dysfunction via AKT/mTOR/HIF-1α/RORγt/IL-17 Signaling and the Gut Microbiota in ETEC K88-Challenged Mice - Xin Xu; Hongwei Zhang; Kun Meng; Hongying Cai; Weiwei Liu; Liye Song; Zihan Zhang; Qijun Zhu; Xiling Han; Yunsheng Han; Peilong Yang (Antioxidants)
Limosilactobacillus reuteri, a recognized probiotic, improves intestinal health in animals, but the mechanism remains unclear. This study investigates the mechanisms by which L. reuteri ZY15, isolated from healthy pig feces, mitigates intestinal barrier damage and inflammation caused by oxidative stress in Enterotoxigenic Escherichia coli (ETEC) K88-challenged mice. The results indicated that L. reuteri ZY15 increased antioxidant capacity by reducing serum reactive oxygen species (ROS) and superoxide dismutase (SOD) levels. L. reuteri ZY15 enhanced the intestinal barrier by upregulating mucin 1, mucin 2, occludin, zonula occludens-1 (ZO-1), and claudin-1 expressions in protein and mRNA levels. It significantly alleviated intestinal inflammation by reducing the proinflammatory cytokines interleukin-1β (IL-1β), interferon-γ (IFN-γ), tumor necrosis factor-α (TNF-α), and interleukin-17 (IL-17) mRNA and protein levels. Notably, L. reuteri ZY15 suppressed intestinal inflammation by inhibiting AKT/mTOR/HIF-1α/RORγt/IL-17 pathway activation. Additionally, it significantly altered the structure of gut microorganisms by enriching Akkermansia and Clostridia_UCG.014, and thereby re-establishing colonization resistance and alleviating ETEC K88-induced intestinal barrier damage and inflammation in mice. Taken together, our findings reveal the protective mechanism of L. reuteri ZY15 in mice challenged with ETEC K88 by regulating AKT/mTOR/HIF-1α/RORγt/IL-17 signaling and microbial imbalance. Leveraging these properties, live L. reuteri ZY15 offers a promising alternative treatment for Escherichia coli-induced diarrhea in weaned piglets.